The Role of Gapoktan Cooperatives Towards Community Economic Empowerment Efforts in Huta Nauli Village - Agustina Mariana Sianipar (Institute of Computer Science (IOCS), 2019)
The underprivileged people often find it difficult to start developing a business that will be cultivated which aims to improve the level of their economy, due to the limited business capital they have. Banks in Indonesia often choose to lend more capital to the upper middle class rather than the lower middle class. That's why not a few people are less able to get caught up in loan sharks. Cooperatives are considered appropriate for the people of Indonesia, especially the poor, because it has a dual way of having economic and social elements, so that not only helps to improve the economy but also pay attention to elements of their social development. This study wants to find out how the role, results for customers as well as cooperative obstacles in improving community welfare, especially in agriculture through business capital loans. Through interviews and observations it can be seen that the stages carried out are quite in accordance with the objectives of community economic empowerment. In this study the approach used is a qualitative approach, with observation, interviews and documentation studies. In interviewing the informant, the writer uses purposive sampling technique in the village of Huta Nauli. From the results of the study it was found that the empowerment carried out by the Gapktan Cooperative in improving the welfare of the community especially in agriculture, they received capital assistance to develop their businesses, even the results of the benefits obtained were used to meet their daily needs and develop their agriculture.